ANALISIS KONTRASTIF BAHASA: URGENSI MEMAHAMI BUDAYA DALAM KAJIAN BAHASA ARAB - Awaliyah, Mursyidatul (TASHWIR, 2022)
Abstract: There is one expression that states that language indicates one's identity, there is also language indicating nation. Language and culture have a coordinative relationship characterized by the quality of the reciprocal relationship between the two, and a subordinate that reflects one quality of the relationship that is only one-sided, meaning that it is the culture that influences the language, and not the other way around. Because of the close relationship between language and culture, there are some experts who equate the relationship between the two inseparable things like two sides of a coin. When learning a foreign language, we also indirectly learn the culture of the language we are learning. Because language reflects the culture of a person. Similarly, when studying Arabic, we also learn the cultural form of native Arabic speakers. Contrastive analysis is very useful in the interests of the development of the language itself, as well as useful for understanding the cultures of other countries through linguistic differences. Contrastive analysis also contributes to the translation to be more accurate in expressing intent in the source language text.Keywords: Arabic; Contrastive Analysis; Culture; Indonesian Language. Abstrak: Ada satu ungkapan yang menyatakan bahwa bahasa menunjukkan identitas seseorang, ada juga bahasa menunjukkan bangsa. Bahasa dan kebudayaan memiliki hubungan koordinatif yang dicirikan dengan kualitas hubungan timbal balik antara keduanya, dan subordinatif yang mencerminkan satu kualitas hubungan yang hanya sepihak, artinya budayalah yang mempengaruhi bahasa, dan bukan sebaliknya.  Karena eratnya hubungan bahasa dan kebudayaan, ada sebagian pakar yang menyamakan hubungan keduanya dua hal yang tidak dapat dipisahkan seperti dua sisi mata uang. Ketika mempelajari bahasa asing maka secara tidak langsung kita juga mempelajari budaya dari bahasa yang kita pelajari. Karena bahasa mencerminkan budaya sesorang. Demikian pula ketika mempelajari bahasa Arab kita juga belajar bgaimana budaya dari penutur asli bahasa Arab. Analisis kontrastif sangat berguna untuk kepentingan pengembangan bahasa itu sendiri, serta berguna untuk memahami budaya negara lain melalui perbedaan linguistik. Analisis kontrastif juga berkontribusi pada terjemahan agar lebih akurat dalam mengekspresikan maksud dalam teks bahasa sumber.Kata Kunci: Analisis Kontrastif; Budaya; Bahasa Arab; Bahasa Indonesia.